SUCCESSFUL TREATMENT OF CHALLENGING CASE OF INFECTIVE ENDOCARDITIS - Milačić, Petar; Nešić, Ivan; Miličić, Miroslav; Mićović, Slobodan (Halo 194 Scientific Journal of Emergency Medicine, 2020)
Introduction: We present a successfully cardiosurgically treated patient with damage to the fibrous heart skeleton caused by advanced infective endocarditis after the replacement of the aortic valve. Case report: Redo procedure was done through median sternotomy using cardiopulmonary bypass. Artificial aortic and native mitral valves were excised and all infected tissues were removed. Reconstruction of the fibrotic cardiac skeleton was done using two autologous pericardial patches according to Tyrone-David. Both mechanical valves were implanted. Conclusion: Successful curing one of the most difficult conditions in cardiac surgery is possible in our country.
Keywords: endocarditis, fibrous heart skeleton, cardiosurgical treatment